Long Term Follow-Up in Gluteal Augmentation Using Cross-Linked Hyaluronic Acid: Up to 20 Months Ultrasound Follow-Up - Renato Pazzini; Renata Viana; Giseli Petrone (Cosmetics)
This article describes a technique for gluteal augmentation using cross-linked hyaluronic acid (HA) filler, with a focus on long-term patient follow-up. The rising demand for buttock enhancement driven by esthetic preferences has led to the exploration of minimally invasive alternatives to traditional surgical methods. Ultrasound imaging was utilised to evaluate the presence and distribution of HA filler over time. The patients reported satisfactory aesthetic improvements, with mild transient side effects. The findings highlight the technique’s effectiveness in achieving enhanced gluteal contour with a minimal volume of filler, demonstrating both safety and durability in the long term. This innovative approach may serve as a valuable option in aesthetic practises focused on body contouring.